2002
DOI: 10.1183/09031936.02.00228502
|View full text |Cite
|
Sign up to set email alerts
|

Acute protection against exercise-induced bronchoconstriction by formoterol, salmeterol and terbutaline

Abstract: The onset of bronchoprotection as obtained by various b 2 -agonists has not been examined in a comparitive study. In this study, the onset of bronchodilation and protection against exercise-induced bronchoconstriction in asthmatics after inhalation of the long-acting b 2 -agonists formoterol and salmeterol and the shortacting b 2 -agonist terbutaline were measured.Twenty-five subjects with asthma and a history of exercise-induced bronchoconstriction (mean baseline forced expiratory volume in one second (FEV1):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 23 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Inhaled β 2 ‐agonists are widely prescribed in the treatment of asthma and are the most effective bronchodilator on human airways [1,2]. In addition to their bronchodilator effect, bronchoprotective properties have also been demonstrated against various stimuli including exercise [3], cold air, methacholine or histamine‐induced bronchoconstriction [4]. The interest in this bronchoprotective effect of β 2 ‐agonists has grown with the introduction of long acting β 2 ‐agonists such as salmeterol or formoterol [5,6] that are taken morning and evening to prevent an asthma crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled β 2 ‐agonists are widely prescribed in the treatment of asthma and are the most effective bronchodilator on human airways [1,2]. In addition to their bronchodilator effect, bronchoprotective properties have also been demonstrated against various stimuli including exercise [3], cold air, methacholine or histamine‐induced bronchoconstriction [4]. The interest in this bronchoprotective effect of β 2 ‐agonists has grown with the introduction of long acting β 2 ‐agonists such as salmeterol or formoterol [5,6] that are taken morning and evening to prevent an asthma crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Formoterol has a fast onset of action, in both asthma [2, 3] and COPD [4,] with a 12-hour effect on spirometry [5, 6]. Studies with the long-acting anticholinergic compound tiotropium demonstrated that an 18-µg dose is safe and provides effective bronchodilation suitable for maintenance therapy in COPD with once-daily dosing [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Being conservative, we hypothesised that the combination of DSCG/REP would be superior to MON even when comparing with the last level pre-exercise, although the reliever (reproterol) might have already enlarged the airways after inhalation at that time. In fact, this "adjusted approach" was also chosen sometimes in the literature on EIA, particularly if the duration of the effect was assessed [22][23][24]. However, other investigations [9,25] used the last value pre-inhalation as baseline (unadjusted approach).…”
Section: Discussionmentioning
confidence: 99%